Review of Permafrost Degradation in the Mongolian Plateau - Fengjiao Li; Juanle Wang; Pengfei Li; Avirmed Dashtseren (Land, 2025)
Permafrost serves as a crucial indicator of global climate change. Its degradation significantly influences Earth’s surface systems, including hydrology, soil, climate, ecosystems, and even civil construction. The distribution of permafrost in the Mongolian Plateau (MP) has an important influence in North Asia and even the Euro-Asia continent. This study provides a comprehensive review of the current state of permafrost degradation and its influence on MP, including climate change and human activities. Remote sensing technologies for permafrost monitoring, including optical remote sensing data models and InSAR technology, are also reviewed. This paper outlines eight future research directions by exploring the latest advancements and technical challenges in permafrost monitoring in the region. These include fundamental investigations of the permafrost zone; evaluation of permafrost effects on ecosystems; hydrology and water resources research; assessment and engineering of freeze–thaw hazards; sustainable regional development in permafrost zones; remote sensing monitoring techniques for permafrost; inter-regional comparative and collaborative research; and data sharing and standardization for permafrost research. This study provides valuable insights into the progress of permafrost degradation not only in the MP but also as a reference for related permafrost studies in other mid-to-high latitudes regions.